2016
DOI: 10.3390/mi7050073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geometry and Surrounding Conditions on Fluid Flow in Paper-Based Devices

Abstract: Fluid flow behaviour in paper is of increasing interest due to the advantages and expanding use of microfluidic paper-based analytical devices (known as µPADs). Applications are expanding from those which often have low sample fluid volumes, such as diagnostic testing, to those with an abundance of sample fluid, such as water quality testing. The rapid development of enhanced features in μPADs, along with a need for increased sensitivity and specificity in the embedded chemistry requires understanding the pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Although many POC diagnostic devices have been fabricated and tested, a transition from academia to industry is mandatory for their commercialization. Generally, these μPADs have the following limitations: (i) sample retention and evaporation issues can cause serious problems with the transportation of sample [119], (ii) variation in the specificity and sensitivity of μPADs is the main concern of the present era because it plays a crucial role in avoiding false-positive results [120], and (iii) reagents used in these μPADs, such as enzymes, antigens, and antibodies, must withstand the harsh environmental conditions met during shipping and storage processes [3,121]. …”
Section: Future Of Paper-based Microfluidic Devicesmentioning
confidence: 99%
“…Although many POC diagnostic devices have been fabricated and tested, a transition from academia to industry is mandatory for their commercialization. Generally, these μPADs have the following limitations: (i) sample retention and evaporation issues can cause serious problems with the transportation of sample [119], (ii) variation in the specificity and sensitivity of μPADs is the main concern of the present era because it plays a crucial role in avoiding false-positive results [120], and (iii) reagents used in these μPADs, such as enzymes, antigens, and antibodies, must withstand the harsh environmental conditions met during shipping and storage processes [3,121]. …”
Section: Future Of Paper-based Microfluidic Devicesmentioning
confidence: 99%
“…Past work has demonstrated that the liquid front observed while liquid is flowing through paper does not indicate that all of the paper behind this front is completely saturated with the liquid (Bico & Quéré 2003). This was also confirmed in a recent study by Walji & MacDonald (2016) where they observed post-wetting flow into paper after the visual liquid front reached the end of the strip. This effect is often attributed to the slower filling of smaller inter-fibre pores as a result of the distribution of pore sizes in a complex fibre matrix like paper.…”
Section: Overviewmentioning
confidence: 63%
“…[10a] Paper is an excellent substrate for automatic multistep processes, since it integrates a passive fluid pumping through the capillary forces of cellulose fibers; however, this property is dependent on not only paper type [116] but also many other parameters. It is dependent on the geometry of the microfluidic channel, [116][117] the presence of wax boundaries, [118] the ambient conditions (such as temperature and moisture), [116,119] the confinement of the space, [33b,120] etc. These articles give insights into the physical mechanisms involved in the passive pumping of paper, making the subject possible to be studied by anyone, since it is observed by the naked eye.…”
Section: Advanced Characterization Of Paper Devicesmentioning
confidence: 99%